Utility of peripheral blood smear in platelet count estimation - Anchinmane, Vyankatesh T.; Sankhe, Shilpa V. (International Journal of Research in Medical Sciences, 2019)
Background: There are several methods of platelet count used in hematology laboratory. These methods are manual counting, automated hematology analyzer counting, platelet count estimation by peripheral blood smear (PBS) method etc. Many diseases such as dengue, malaria, pregnancy induced hypertension etc. may leads to severe thrombocytopenia. Timely and precise diagnosis of platelet count plays very crucial role in critical care management of thrombocytopenia cases. The present study was undertaken to estimate platelet counts by PBS method and correlate them with results from automated hematology analyzer method. Methods: Study included one hundred randomly collected blood samples in EDTA anticoagulant vacutainer tubes. Each blood sample was processed for platelet count estimation with automated hematology analyzer and Leishman’s stained PBS examination. The statistical analysis was done by using Pearson’s correlation test to access the agreement between both the methods. Results: The Pearson’s correlation test showed significant positive correlation for platelet count estimation between both the methods. (r =0.9789). Conclusions: Platelet count estimation by PBS method is reliable and statistically significant when compared to hematology analyzer method. PBS platelet estimation method can be taken as early and rapid procedure for platelet assessment in critical severe thrombocytopenia cases. This method is simple, cheaper and can be done in rural hospital setup where automation is not available.